Does salivary cortisol serve as a potential biomarker for temporomandibular disorders in adults? - Lujain AlSahman; Hamad AlBagieh; Roba AlSahman; Noshir R. Mehta; Leopoldo P. Correa (BMC, 2024)
Abstract Background The etiology of temporomandibular disorders (TMD) is multifactorial, involving a complex interplay of psychological and physiological factors. While salivary biomarkers, particularly cortisol, play an important role in TMD pathophysiology, evidence in the literature is still scarce and inconsistent. Hence, this study aims to evaluate the applicability of salivary cortisol as a potential biomarker for TMD in adults. Methods The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) were used to accurately diagnose TMD patients. The study included adults, both male and female, aged 18-40 in the TMD group (n = 66) and non TMD participants (n = 66) matched for age and gender. Salivary samples were collected from participants at two time points: early and late morning. Cortisol levels in the samples were quantified using enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using a one-way ANOVA to evaluate the correlations between cortisol levels and the study variables. Tukey's post-hoc tests were applied to adjust for multiple comparisons. Results Salivary cortisol levels were significantly higher in the TMD group than in the corresponding controls (p = 0.034). In the TMD group, the mean cortisol levels early in the morning were 29.95 ± 75.05 (0-398.64), while the late morning levels were recorded as 4.87 ± 3.96 (0-17.13). In the control group, the mean cortisol levels early in the morning were 10.98 ± 16.83 (2.16-92.90), and late morning mean cortisol levels were 6.15 ± 6.13 (0-20.42). This indicates that the early morning levels of cortisol are higher in TMD patients (p = 0.046). In the subgroup analysis of the TMD, the mean salivary cortisol levels recorded were highest at 82.49 ± 124.34 (8.32-398.64) in patients having disc displacement without reduction with limited mouth opening. Furthermore, the mean salivary cortisol levels in the early morning were statistically higher (84.83 ± 132.80) in males compared to females (9.36 ± 9.01) (p = 0.008) with TMD. Conclusion The result of this study suggests that salivary cortisol could be a potential biomarker for a specific TMD subtype (disc displacement without reduction with limited mouth opening). However, further studies are needed to better understand the role of cortisol biomarker in the underlying pathogenesis of TMD.